Pengembangan Aplikasi Berbasis Android untuk Pemantauan Masalah dalam Kegiatan Praktik Kerja Industri Siswa di SMK Negeri 2 Malang Berdasarkan Model Extreme Programming (LAPAN) - Naufal Nuha Ardhana; Retno Indah Rokhmawati; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Industrial Internship (hereinafter referred to as "PRAKERIN") is a program in which students experience hands-on industrial works. PRAKERIN need daily monitoring, which cant be fulfilled by SMK Negeri 2 Malang, resulting students being sent back to the school due to the lateness of problem solving. A user-friendly PRAKERIN monitorial application is needed. Researcher applies the Extreme Programming Method, a development method in which the plannings, designings, implementations and trials are repeated, making it possible to conduct modifications. This research consists of two iterations and involving four actor that is Admin, Teacher, Preceptor, and Student. In the first iteration, Black-Box Testing showed that application has 23 valid functionals with validity rate on 100%. At the same time, Usability type User Acceptance Test showed that application has usability rate on 87,50%. In the second iteration, it is known that additional functionals are proven valid with validity rate on 100%. At the same time on the Usability aspect showed that application has usability rate on 88,46%. Analysis result in both iteration showed that the application has been successfully developed, with validity rate on 100%. Because the functional which manage problem and attendance is proven valid, it can be said that problem monitory activity in PRAKERIN is successfully made easy. At the same time, analysis result on Usability aspect both iteration showed that the application has usability rate on 88,46%, meanings that it is very easy to use.